(untitled) (Research, Society and Development, 2024)
Obesity is a multifactorial disease related to several genetic, metabolic, psychosocial and environmental factors. After the emergence of the COVID-19 pandemic, this condition of excess weight was recognized as a risk factor for the progression of the disease to a more severe form, causing a worse prognosis in children. Thus, the objective of the present work was to address the increase in pediatric obesity and its relationship with the COVID-19 pandemic. To carry out this literature review study, articles that related the diagnosis of PU in children and their difficulties. Thus, of the 30 articles found in the VHL database, only 12 were used, as they contained what was necessary for the research. Risk factors were observed that, during the pandemic, are directly related to the topic. Among them, sedentary lifestyle, less structured days, increased boredom and poverty and male sex were highlighted. Furthermore, consequences such as cardiovascular changes, type 2 diabetes, obstructive sleep apnea, non-alcoholic liver disease and psychosocial problems were noted in this study. Therefore, given that childhood obesity is a clinically significant problem and that, during the period of the coronavirus pandemic, there was an increase in the number of cases, more studies along the same lines are needed to gain a deeper understanding of the increase in pediatric obesity and its relation with the COVID-19 pandemic.